Social condition of japanense geisha as reflectd in short story Madame Butterfly by John Luther Long - Basri, Hasan (COMMICAST, 2021)
In this undergraduate thesis, the writer discusses short story Madam Butterfly written by John Luther Long. This study is aimed: (1) to describe the Geisha social life condition in Japanese society as reflected in Madame Butterfly (2) to describe the social class in Japanese society in 1903s as reflected in Madam Butterfly. In doing this research, the writer uses descriptive qualitative method which refers to description of things, characters, meaning and symbols. There are two types of data in this study.The findings of the research show that Geisha in Japan through Cho Cho San the main character in Madame Butterfly was a reflection of Geishaâ€™s life condition in Japanese society. The writer conclude that Social condition of Geisha in Japan in 1930s are an entertainer because they are has been train for accompany all of the guests. Serve the drink, singing, dancing and playing music instrument were the Geishaâ€™s job while accompany the guest. The guest also did some flirting to the Geisha. In 1930s American missionary and American Navy enter Japan for some mission, there are also American people who married Japanese girl. Beside the Geisha social life condition, there are two class in Japanese society that exist in 1903s Kazoku (Nobleman) and Heinin (Proletar). The social class in Japan in that time is very contrast between the Nobleman and Ploretar. Madam Butterfly include to high class people because of she married to a foreigner because according to Japanese, if they married a foreigner it can rise their social status.Â